PENGARUH MODAL, TENAGA KERJA, BIAYA BAHAN BAKU DAN USIA TERHADAP PRODUKSI TIKAR DI KECAMATAN JANGKA KABUPATEN BIREUEN - Mulyanti Mulyanti; Umaruddin Usman (Jurnal Ekonomi Pertanian Unimal, 2020)
The purpose of this study is to see the effect of capital, labor, raw material costs and age on the production of Mats in the Jangka District of Bireuen Regency. The study uses primary data sourced from 54 respondents. This study employes multiple linear regression. The results of the studi showed that capital has a positive and significant effect on production, labor has a positive and significant effect on production, raw material costs has a positive and significant effect on production and age negatively effect on production but together with capital, labor, raw material costs and age variables have a positive effect on production.